1982
DOI: 10.1128/jb.150.2.785-787.1982
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular siderophores of rapidly growing Aspergillus nidulans and Penicillium chrysogenum

Abstract: The highly active extracellular siderophores previously detected in young cultures of Aspergillus nidulans and Penicillium chrysogenum have been identified as the cyclic ester fusigen (fusarinine C), and its open-chain form, fusigen B (fusarinine B).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0
1

Year Published

1988
1988
2020
2020

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 10 publications
1
6
0
1
Order By: Relevance
“…In our previous study, we detected neither ferricrocin nor ferrirhodin but, instead, found exclusively TAFC after 48 h of growth under iron-depleted conditions (Haas et al, 1999). This is in accordance with data from Charlang et al (1981;1982), who proved that older cultures of A. nidulans produce TAFC and that young cultures additionally excrete the unacetylated form of TAFC, fusigen (fusarinine C), which disappears in older cultures. Reversed-phase high-performance liquid chromatography (HPLC) analysis according to the method of Konetschny-Rapp et al (1988) confirmed that young A. nidulans cultures excrete fusigen, with the highest amount produced at 24 h of growth ( Fig.…”
Section: Resultssupporting
confidence: 91%
“…In our previous study, we detected neither ferricrocin nor ferrirhodin but, instead, found exclusively TAFC after 48 h of growth under iron-depleted conditions (Haas et al, 1999). This is in accordance with data from Charlang et al (1981;1982), who proved that older cultures of A. nidulans produce TAFC and that young cultures additionally excrete the unacetylated form of TAFC, fusigen (fusarinine C), which disappears in older cultures. Reversed-phase high-performance liquid chromatography (HPLC) analysis according to the method of Konetschny-Rapp et al (1988) confirmed that young A. nidulans cultures excrete fusigen, with the highest amount produced at 24 h of growth ( Fig.…”
Section: Resultssupporting
confidence: 91%
“…Here is the first study to report the bacterial fusarinine. Ornithine is the only amino acid of fusarinine (Charlang et al, 1982). The Kyoto Encyclopedia of Genes and Genomes (KEGG, https://www.kegg.jp/) shows that fusarinine can be synthesized by some specific ornithylesterases including fusarinine-C ornithineesterase, ornithine esterase and 5-Nacyl-L-ornithine-ester hydrolase.…”
Section: Discussionmentioning
confidence: 99%
“…nidulans and A . fumigatus [ 46 , 51 , 52 ], exclusively fusarinine C by Fusarium roseum and F . oxysporum [ 29 , 53 ] and coprogens by N .…”
Section: Discussionmentioning
confidence: 99%